Enhancing the role of educational technology by adopting new technology in higher learning institution: UTM experiences - Ali, Mohamad Bilal (2012)
The First International Seminar on Quality and Affordable Education (ISQAE 2012) on May 21-23, 2012 at Grand Sahid Hotel, Jakarta. ISQAE 2012 will focus on “Developing a Qualified and Affordable Education System for All”. ISQAE 2012 is organized by Jakarta State University, University of Malaya and Universiti Teknologi Malaysia. The seminar aims pruducing the formulation strategies and facilitating a dialogue to solve how to develope a qualified and affordable education system for all level society.